Phenomenological implications of Bohr space in six dimensions - Georgoudis, P. (HNPS Advances in Nuclear Physics, 2019)
The critical point for a second order shape/phase transition in the structural evolution of atomic nuclei, the consequences on the mass parameter and its irrotational flow are discussed after the embedding of Bohr space in six dimensions.